2004
DOI: 10.1590/s1516-35982004000700020
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de suplementação com sal mineral proteinado para novilhos Nelore terminados em pastagem no período de baixa produção forrageira

Abstract: RESUMO -Foram avaliados dois níveis de suplementação com sal mineral proteinado (290 e 400 g.an -1 .dia -1 ), em comparação ao sal mineral, em 90 novilhos Nelore, mantidos em pastagem de grama estrela roxa (Cynodon plectostachyus Pilger) no inverno. O consumo do suplemento foi ajustado pelo teor de cloreto de sódio adicionado à mistura. Quando considerado o período de adaptação (28 dias) na análise estatística, não foi observada diferença no ganho médio diário (GMD) entre os tratamentos, ao passo que, quando d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
21

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
(10 reference statements)
0
8
0
21
Order By: Relevance
“…In this case, the use of protein or multiple supplements may increase the productive performance of animals. In this research study, results showed lower productive performance than that found by Ruas et al (2000), Zanetti et al (2000), Moreira et al (2004), Moraes et al (2006), who reported higher productive performance for beef cattle receiving protein or multiple supplementation. Higher total dry matter intake found in studies carried out by Ruas et al (2000) and Zanetti et al (2000) may justify those results.…”
Section: Resultsmentioning
confidence: 41%
See 3 more Smart Citations
“…In this case, the use of protein or multiple supplements may increase the productive performance of animals. In this research study, results showed lower productive performance than that found by Ruas et al (2000), Zanetti et al (2000), Moreira et al (2004), Moraes et al (2006), who reported higher productive performance for beef cattle receiving protein or multiple supplementation. Higher total dry matter intake found in studies carried out by Ruas et al (2000) and Zanetti et al (2000) may justify those results.…”
Section: Resultsmentioning
confidence: 41%
“…Higher total dry matter intake found in studies carried out by Ruas et al (2000) and Zanetti et al (2000) may justify those results. However, a study by Moreira et al (2004) found higher dry matter intake of supplement. Probably, supplement dry matter intake (58 to 142 g day -1…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In this study, concentrate supplementation containing high levels of protein may be an important tool to increase dry matter intake and digestibility of fibrous fractions of forage, also to improve the productive performance of lambs in the rainy-dry transition period and in dry period of year (MORAES et al, 2006;MOREIRA et al, 2004;RUAS et al, 2000;ZANETTI et al, 2000). In the present trial, the CP level used in concentrate was 20.0% of DM.…”
Section: Resultsmentioning
confidence: 97%